Pengaruh Pola Asuh Orang Tua Terhadap Sikap Tanggung Jawab dalam Pembelajaran Daring di SDN Kota Bengkulu - Irfan Supriatna; Victoria Karjiyati (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2021)
This study aims to analyze the effect of authoritarian, democratic, and permissive parenting on the responsible attitude of fifth graders in online learning at SDN Bengkulu City. This type of quantitative research with comparative causal research method. The population of this study were all fifth grade students at SDN Bengkulu City, totaling 114 students. The sample in this study were 29 students from 114 populations. The data collection technique used a parenting style questionnaire consisting of 35 items and a student responsibility attitude questionnaire consisting of 27 items. The data analysis technique in this study used simple linear regression. The conclusion in this study is that there is an influence of parenting style on students' responsible attitudes and there is also an influence of parenting style on aspects of authoritarian and democratic parenting on students' responsible attitudes, while permissive parenting has no effect on responsible attitudes.